Pendidikan Multikultural-Religius untuk Mewujudkan Karakter Peserta Didik Yang Humanis-Religius - Arifin, Zainal (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
The term multicultural education, religious education contains two concepts combined, i.e between multicultural education and religious education. Multicultural education as the basis of education values cultural diversity. Whereas, the religious education is as a basis of education on religious values to produce religious men. The combination of these two concepts of education aims to make an educational system that integrates from both of them, or reduce the advantages, especially to produce religious humanist students in a good character.